Peran Pemerintah Daerah dalam Penanggulangan Bencana Banjir di Kota Sukabumi - Ni Putu Juwanita Dewi; Anggi Nugraha (University of Merdeka Malang, 2026)
High rainfall intensity can cause flooding, including the flooding that occurred in Sukabumi City. Residents of Sukabumi City suffered significant losses. The local government needs to play a role in flood disaster management in their area. The main objective of this study is to analyze the role of the local government in flood disaster management and to identify supporting and inhibiting factors, along with solutions for flood disaster management in Sukabumi City. This study uses an empirical juridical method, namely a legal research method that utilizes empirical facts obtained from interviews and actual behavior through direct observation. The results of this study indicate that the local government's implementation is not optimal due to obstacles such as limited budget, human resources, and facilities, egocentricity between agencies, and public awareness of flood prevention. This study recommends that the local government increase its budget allocation to increase the necessary human resources and facilities and optimize its outreach program to the community through community forums or disaster-resilient villages on an ongoing basis.